Growth and development of ‘sweet net 9’ melon (Cucumis melo L.) in NFT hydroponics as affected by pruning leaves below fruits and foliar application of potassium sulphate (K2SO4) - Pramono, Mellinia Valentiningtyas; Sulistyaningsih, Endang; Murti, Rudi Hari (Jurnal Ilmu Pertanian, 2025)
Leaf pruning reduces resource competition, directing assimilates to fruit development, while aging plants require supplemental K to support nutrient uptake. This study aimed to evaluate the effects of pruning leave below fruits and foliar application of K₂SO₄ on fruit weight and quality. The experiment was conducted over three months (October–December 2024) in a screenhouse at Pondok Pesantren Aqwamu Qila, Bantul, Yogyakarta. Sampling and analysis were carried out at the Crop Production Management Laboratory, Faculty of Agriculture, Universitas Gadjah Mada. A split-plot design was used with two factors, namely K₂SO₄ concentrations (0, 1, 2, 3 g/L) as the main plot and pruning (with/without) as the subplot, resulting in 8 treatment combinations replicated in 3 blocks. Data were analyzed using split-plot ANOVA in R-Studio, followed by DMRT at a 95% confidence level when significant differences were found. The study showed that pruning significantly increased leaf length (16.49%) and width (20.89%). The application of 0 g/L K₂SO₄ produced the highest harvest index (0.49), though not significantly different compared to that of 2 g/L and 3 g/L. Combining leaf pruning with 2 g/L K₂SO₄ resulted in a high leaf area and LAI (5.68), comparable to non-pruned plants with 3 g/L K₂SO₄ (5.83). This combination also yielded the highest fruit potassium content (1.90%) but lowered fruit sweetness (8.65 ˚Brix). The elevated potassium content may provide health benefits, particularly in reducing blood pressure.